Local Knowledge System of Milkfish Farmers at Traditional Pond in Tassiwalie Coastal Village Pinrang District - Agusanty, Harnita; Arief, Andi Adri; ., Kasri; ., Kasifah (Torani Journal of Fisheries and Marine Science, 2021)
Development of milkfish aquaculture in traditional ponds must of course be based on its potential. One of the most important potentials is the local knowledge of the community about the aquaculture system in ponds. The purpose of this research is to analyze the behavior and local knowledge of traditional farmers in managing their aquaculture business which is influenced by elements of local culture that penetrate into the social system of society. This type of research is qualitative with a case study approach. Data collection was carried out through direct observation and in-depth interviews with a number of informants. The process provides a comprehensive description of the actions and practices in managing traditional pond businesses. There were 27 informants as the primary data source. Analysis through content analysis from the compilation of interviews with technique snowball by still referring to the principle of triangulation. The results showed that local knowledge, method technology, and traditional aquaculture practices, farmers still did because they still were considered functional and effective. Modern aquaculture technologies have not been able to replace most of the main functions of these local practices. The effectiveness of function is shown through the recognition of farmers that with traditional technology, they can carry out their aquaculture business activities and obtain the main source of income from the past to the present.  Existing local knowledge is closely related to customary beliefs as norms that regulate social interactions.